2018
DOI: 10.1038/s41598-018-27864-6
|View full text |Cite
|
Sign up to set email alerts
|

GRAMD1B regulates cell migration in breast cancer cells through JAK/STAT and Akt signaling

Abstract: Dysregulated JAK/STAT signaling has been implicated in breast cancer metastasis, which is associated with high relapse risks. However, mechanisms underlying JAK/STAT signaling-mediated breast tumorigenesis are poorly understood. Here, we showed that GRAMD1B expression is upregulated on IL-6 but downregulated upon treatment with the JAK2 inhibitor AG490 in the breast cancer MDA-MB-231 cells. Notably, Gramd1b knockdown caused morphological changes of the cells, characterized by the formation of membrane ruffling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…The previously mentioned Wwox can inhibit breast cancer metastasis by preventing receptor binding [35]. Furthermore, Kim et al have demonstrated that Mesodermspecific transcript (MEST) induces Twist expression by activating the JAK/STAT3 signaling pathway [51], whereas Khanna et al have shown the inhibition of GRAM domain-containing protein 1B (GRAMD1B) in breast cancer migration via the suppression of the JAK/ STAT3 and protein kinase B (Akt) pathway [52]. Instead of classical ligand/receptor binding in the plasma membrane for STAT3 activation, a new pathway is found in which OSM/SMAD3 could also activate STAT3 and mediate Snail expression and promote epithelialmesenchymal transition (EMT) in breast cancer, indicating a distinct route of STAT3 activation through cytoplasmic molecules and endogenous signaling [53].…”
Section: The Role Of Stat3 In Breast Cancer Metastasismentioning
confidence: 99%
“…The previously mentioned Wwox can inhibit breast cancer metastasis by preventing receptor binding [35]. Furthermore, Kim et al have demonstrated that Mesodermspecific transcript (MEST) induces Twist expression by activating the JAK/STAT3 signaling pathway [51], whereas Khanna et al have shown the inhibition of GRAM domain-containing protein 1B (GRAMD1B) in breast cancer migration via the suppression of the JAK/ STAT3 and protein kinase B (Akt) pathway [52]. Instead of classical ligand/receptor binding in the plasma membrane for STAT3 activation, a new pathway is found in which OSM/SMAD3 could also activate STAT3 and mediate Snail expression and promote epithelialmesenchymal transition (EMT) in breast cancer, indicating a distinct route of STAT3 activation through cytoplasmic molecules and endogenous signaling [53].…”
Section: The Role Of Stat3 In Breast Cancer Metastasismentioning
confidence: 99%
“…The Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway is implicated in the development and progression of many cancers [1,2] . Hyperactivation of STAT transcription factors, has been reported in both hematologic malignancies and solid tumors, including cancers of the breast, lung, liver, head and neck, and stomach, among others [3][4][5][6][7][8] . For many of these cancers, increased activation of the JAK/STAT signaling pathway is associated with a worse prognosis, including increased recurrence and reduced overall survival [1,9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that activation of PI3K/AKT signaling increases MGP expression (Mirsaidi et al , 2017; Ponnusamy et al , 2018). Although the crosstalk of JAK2/STAT5 signaling and PI3K/AKT signaling has been reported (Britschgi et al , 2012; Khanna et al , 2018), the underlying mechanisms remain largely unknown. Our study used multiple lines of evidences supporting MGP as a novel transcriptional co‐activator of STAT5.…”
Section: Discussionmentioning
confidence: 99%